Bones, Glands, Ears and More: The Multiple Roles of FGF10 in Craniofacial Development - Prochazkova, Michaela; Prochazka, Jan; Marangoni, Pauline; Klein, Ophir D. (Frontiers in Genetics, 2018)
Members of the Fibroblast Growth Factor (FGF) family have myriad functions during development of both non-vertebrate and vertebrate organisms. One of these family members, FGF10, is largely expressed in mesenchymal tissues and is crucial for postnatal life because of its critical role in development of the craniofacial complex, as well as in lung branching. Here, we review the function of FGF10 in morphogenesis of craniofacial organs. The dysregulation or absence of FGF10 function affects the process of palate closure, and FGF10 is also crucial for development of salivary and lacrimal glands, the inner ear, eye lids, tongue taste papillae, teeth and skull bones. Mutations within the FGF10 locus have also been described in connection with craniofacial malformations in humans. A detailed understanding of craniofacial defects caused by dysregulation of FGF10 and the precise mechanisms that underlie them offers new opportunities for development of medical treatments for patients with birth defects and for regenerative approaches for cancer patients with damaged gland tissues.